A Novel Overdenture Telescopic Prosthesis - Modalavalasa, Hari Krishna; Shankar, Y Ravi; Kumar, P Shameen; Kumar, T Satyendra (Journal of Orofacial Research, 2015)
Preventive prosthodontics emphasizes the importance of any procedure that can delay or eliminate future prosthodontic problems. In the past when patients presented themselves as candidates for a dentures, teeth were extracted but in the overdenture, a complete or partial denture prosthesis constructed over existing teeth or root structure, is not a new concept in a technical approach to a prosthodontic problem, but an old concept. The present article focuses on a novel approach in fabricating overdenture by incorporating partial denture framework along with metal copings.